Neurological polymorphism of systemic lupus erythematosus - A. A. Garmanova; A. M. Morozov; Yu. E. Minakova; M. A. Belyak (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Damage to the nervous system during the progression of systemic lupus erythematosus (SLE) is not only one of the most common phenomena, but also an unfavorable prognostic criterion for the patient. At the moment, more than 19 types of neurolupus manifestations are known in both adult patients and children. The main problem is the non-specificity and variability of neuropsychiatric symptoms, which can be associated not only with the pathogenesis of SLE, but also with other factors caused by the influence of the environment, psychosomatics, and concomitant diseases. Currently, there is no "gold standard" for diagnosing this type of pathology, and sometimes the selection of therapy does not correspond to the etiology of the lesion. Also, the urgency of this problem proves the lack of a clear classification of neurological complications of SLE, which can be used by specialists at the present time. The links of the pathogenesis of the development of both systemic lupus erythematosus itself and lesions of the nervous system in this disease are not fully understood. The purpose of this study. To study the pathogenesis and symptomatic manifestations of neurolupus, presented in the studies of Russian and foreign scientists, with the subsequent systematization of the information obtained. Material and methods. A study was made of materials from foreign and domestic literature of recent years on the issue of classification, pathogenetic and symptomatic problems of the neurological manifestation of systemic lupus erythematosus. Results. The prevalence of neurolupus among SLE patients reaches 95% of cases, expressed both in a single syndrome and in multiple simultaneous clinical manifestations. Lesions of both the central and peripheral nervous systems, as well as psychological disorders, are caused by the toxic effect of actively produced cytokines and interleukins, the deposition of immune complexes and thrombotic vasculitis, an increase in the BBB permeability and the penetration of autoantibodies tropic to the structures of the nervous tissue through it. At the moment, the classification of 2018 most fully covers all possible morphological manifestations of neurolupus, highlighting focal and diffuse lesions of the central nervous system, as well as peripheral. The most common occurrence among SLE patients is headache, which is not a specific manifestation, strokes, aseptic encephalomyelitis, cognitive disorders and depression. Conclusions. Neurolupus is a very common and poorly understood complication of systemic lupus erythematosus, which needs more detailed coverage in the medical literature. With a wide polymorphism of clinical manifestations, the neuropsychiatric syndrome of SLE is a real threat to the patient's life. The lack of a clear classification in clinical guidelines, huge gaps in knowledge about the pathogenesis of nervous pathologies, the similarity of the clinical picture of other diseases and the undeveloped diagnostic tactics of this pathology can lead to ineffectiveness of the therapy, irreversible damage to the nervous tissue and even death.